A focused issue on competence perspectives on new industry dynamics - Sanchez, Ron; Heene, Aimé (Research in competence-based management, 2012)
This volume focuses on Competence Perspectives on New Industry Dynamics. Research in Competence-Based Management (RCBM) is a peer-reviewed title for the publication of papers that extend current competence-based management (CBM) theory, propose new additions to CBM theory, suggest new directions for CBM theory development, and/or apply CBM theory in research on management issues and topics.